NMR in drug design - Craik, David James (CRC Press, 1996)
NMR in Drug Design discusses the use of nuclear magnetic resonance (NMR) in studies of the design, structure, mechanism, and actions of pharmaceutical agents. Topics include rational drug design, NMR techniques in drug design, conformational analysis by NMR, macromolecular structure determination, protein-ligand interactions, drug-DNA interactions, and studies of enzyme mechanisms by NMR. This reference book provides invaluable practical information to the scientist working in drug design or NMR research.
Keywords: farmacie a farmakologie